Virtuous or Villainess? The Image of the Royal Mother from the Early Medieval to the Early Modern Era - Fleiner, Carey; Woodacre, Elena; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This collection addresses royal motherhood across Europe, from both the medieval and Early Modern periods, including (in)famous and not-so-famous royal mothers. The essays in this collection reveal the complexities and the subtleties inherent in the role of royal mothers and challenges these traditional stereotypes. The volume provides a fresh re-evaluation of these women, from those who have been given an almost saintly status to those who struggled against contemporary chronicles and propaganda that perpetuated the stereotypes associated with 'bad mothers'- these particular images of saintliness and wickedness have persisted right into the modern era. This series of intriguing case studies reveals how royal mothers were perceived by their contemporaries and explores the motivation for the ways in which they are depicted in modern popular culture. Taken together with the companion volume, Royal Mothers and their Ruling Children, this collection sheds new light on the important and challenging role of mothers within the framework of monarchy and at the epicenter of power.
.Introduction Carey Fleiner -- .Part One: Fashioning the image of the 'good' and 'bad' royal mother -- .Empress Theodora: A Holy Mother Kriszta Kotsis -- ."Mother of heroes, most beautiful of mothers": Mathilda of Flanders and royal motherhood in the eleventh century Laura L. Gathagan -- .A mother and her illustrious off-spring: The role of Philippa of Lancaster, queen of Portugal, in her children's education (1387-1415) Manuela Santos Silva -- ."Greatest in her offspring": Motherhood and the Empress Matilda Charles Beem -- .Maternal Abandonment and Surrogate Caregivers: Isabella of Angoulême and her Children by King John Louise J. Wilkinson -- .The Perils of Promotion: Maternal Ambition and Sacrifice in the life of Joan of Navarre, Duchess of Brittany and Queen of England Elena Woodacre -- .Part Two: The legacy and reputation of royal mothers-from their contemporaries to the present day -- ."Margaret R": Lady Margaret Beaufort's self-fashioning and female ambition Sally Fisher -- .Playing the Catalan: The Rise of the Chess-Queen; Queenship and Political Motherhood in Late Medieval Aragon and France Zita Rohr -- .Outlander, Baby Killer, Poisoner? Rethinking Bona Sforza's Black Legend Katarzyna Kosior -- .The Empress Matilda and Motherhood in Popular Fiction, 1970's to the Present Katherine Weikert -- .
Keywords: Europe-History-476-1492.; History of Medieval Europe